Analisis Manajemen Strategis Untuk Meningkatkan Daya Saing UMKM di Era Transformasi Digital - Shofia Nawang Hayyuni; Tina Dwi Sri Martiani; Abdul Wahid Al Farizi (Ikatan Da'i Indonesia, 2026)
Advances in digital technology have led to significant changes in the way businesses operate and increased competition in various sectors, including Micro, Small, and Medium Enterprises (MSMEs). This situation forces MSMEs to implement efficient strategic management to survive and increase their competitiveness in the digital era. This study aims to explore the role of strategic management in strengthening MSME competitiveness using the Systematic Literature Review (SLR) method. Data were obtained from 20 national scientific articles published between 2021 and 2025 and selected through Google Scholar based on predetermined inclusion criteria. The study findings indicate that the implementation of digital strategies, business innovation, digital marketing, and the regular use of information technology have a positive effect on increasing MSME competitiveness. However, low digital literacy and limited human resources remain major obstacles in the digital transformation process. This study concludes that strategic management is a crucial framework that not only supports technology adoption but also influences the extent to which technology can drive the sustainability and optimal growth of MSMEs.